Case report: Pellagra presentation with dermatitis and dysphagia - Mengistu, Segenet Bizuneh; Ali, Iman; Alemu, Hiwot; Melese, Endalkachew Belayneh (Frontiers in Medicine, 2024)
Pellagra is a disorder caused by a deficiency of niacin or tryptophan, manifested by characteristic dermatitis on sun-exposed areas of the skin. Gastrointestinal involvement is common, and symptoms include glossitis, stomatitis, and diarrhea. Neurologic symptoms can occur in some patients, including dementia, anxiety, depression, tremors, hyporeflexia and, in severe cases, encephalopathy. We present the case of a woman with hyperpigmentation and hyperkeratosis on sun-exposed areas of the skin along with progressive dysphagia. Notably, she did not report diarrhea or any neurologic or psychiatric symptoms. Her symptoms were most consistent with pellagra, and niacin supplementation was initiated, leading to recovery. This case report highlights that dermatitis and dysphagia, the main gastrointestinal manifestations, can be the only symptoms in patients with pellagra, requiring a high index of suspicion in dermatologic settings to diagnose and treat this fatal condition early.